A bile acid protects against motor and cognitive deficits and reduces striatal degeneration in the 3-nitropropionic acid model of Huntington's disease - Keene, CD (2015)
There is currently no effective treatment for Huntington's disease (HD), a progressive, fatal, neurodegenerative disorder characterized by motor and cognitive deterioration. It is well established that HD is associated with perturbation of mitochondrial e